Project Profile: Modernization of the Veterinary Services División Ministry of Agriculture and Lands: Jamaica - Instituto Interamericano de Cooperación para la Agricultura (IICA) (IICA, 2020)
The IICA evaluation reviewed the operation and management of the VSD and furnished recommendations with respect to a new organizational structure. This new structure covers areas such as increase in the cadre of staff at all levels, the restructuring and de-centralization of the operations of the VSD in order to provide much need services such as island-wide veterinary clinical care, improved laboratory services, improved customer service delivery and provision for training and staff mobility. The proposed project for the Modernization of Jamaica's Veterinary Services Division has incorporated the recommendations of the studies conducted by the OIE and IICA. The final outcome expected from the implementation of the project is the transformation of the VSD into one that will deliver effective and efficient veterinary services to all stakeholders through the implementation of a new organizational structure focusing on personnel development and capacity building, customer service, disease surveillance, quarantine and laboratory services, infrastructure and equipment improvement.